Efektifitas Pijat Woolwich terhadap Pengeluaran Air Susu Ibu (ASI) - Salsabil Rajihah; Fatma Jama; Nur Ilah Padhila (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2026)
Mother's Milk (ASI) is a liquid that provides the most important nutrition needed by babies, serving as natural nutrition because it contains the energy and substances necessary during the first six months of a baby's life. This study aims to determine the effect of Woolwich Massage on Milk Expenditure in Breastfeeding Mothers at the Moncongloe Health Center, Maros Regency. This research employs quantitative research methods within a pre-experimental research design, specifically a pre-test post-test design. The population in this study consisted of 74 individuals at the Moncongloe Health Center in Maros Regency, with a total sample size of 58 respondents. This sampling technique uses purposive sampling. The statistical test used the Wilcoxon test to determine the ratio of milk production before and after treatment. The results of this study showed that before the Woolwich massage, the majority of milk expenditure was in the 'Less ASI' category, and after the Woolwich massage, the majority of ASI expenditure was in the 'Enough ASI' category. Wilcoxon test results obtained a p-value of 0.000 (p-value < 0.05). The conclusion from this study is that Woolwich massage has an effect on breastfeeding mothers at the Moncongloe Health Center in Maros Regency. Therefore, through this research, it is hoped that the community, especially breastfeeding mothers, can apply Woolwich massage as a method to facilitate their breastfeeding